Interferon-Inducible Transmembrane Protein 3-Containing Exosome as a New Carrier for the Cell-to-Cell Transmission of Anti-Brucella Activity - Yi, Jihai; Wang, Yueli; Zhang, Huan; Deng, Xiaoyu; Xi, Jing; Li, Honghuan; Yang, Ningning; Ma, Zhongchen; Wang, Yong; Chen, Chuangfu (Frontiers in Veterinary Science, 2021)
Exosomes are small extracellular vesicles that are released from cells and that function in intercellular communication. Recently, interferon-inducible transmembrane protein 3 (IFITM3) has been identified as a highly effective anti-intracellular pathogen protein that can inhibit the invasion of a wide range of pathogenic microorganisms. However, whether Brucella infection induces secretion of exosomes and whether these exosomes contain IFITM3 protein remain unknown. Here we focused on the immune function of extracellular IFITM3 protein in the process of Brucella infection. This study is the first to show that Brucella melitensis strain M5 (Brucella M5) can stimulate macrophages to secrete large amounts of exosomes. Most importantly, we identified exosomes from Brucella M5-infected cells that were rich in molecules of IFITM3, and these exosomes could transmit the IFITM3 from one cell to another, thereby effectively inhibiting intracellular survival of Brucella. Moreover, immunization with exosomes carrying IFITM3 decreased mouse spleen tissue damage and spleen CFU, leading to the establishment of an anti-Brucella state in mice. In conclusion, our findings provide new insights into the anti-Brucella mechanism of IFITM3-containg exosomes, thus providing a theoretical foundation for systematic elaboration of the mechanisms of Brucella infection and host immunity. The results provide new ideas for the development of candidate vaccines for Brucella.